2013
DOI: 10.1002/jgra.50414
|View full text |Cite
|
Sign up to set email alerts
|

Field‐aligned current loop model on formation of sporadic metal layers

Abstract: [1] This paper proposes a new mechanism for the formation of the sporadic layers by metallic ions as well as metallic atoms in the lower thermosphere and upper mesosphere. The mechanism is based on sporadic occurrence of an electric current loop consisting of the magnetic field-aligned current (FAC) and horizontal Pedersen current in the ionosphere connected with the FAC. The essential point of the present mechanism is the existence of the horizontal electric field convergence at the foot of the upward FAC reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Kirkwood and von Zahn , ]. In addition to this, the ionospheric current accompanied by the electric field may induce horizontal redistribution (including concentration) of the ions [ Matuura et al , ]. As mentioned in the previous section, we found the ionospheric/auroral activities at south side of Syowa Station around the onset of the event.…”
Section: Discussionsupporting
confidence: 67%
“…Kirkwood and von Zahn , ]. In addition to this, the ionospheric current accompanied by the electric field may induce horizontal redistribution (including concentration) of the ions [ Matuura et al , ]. As mentioned in the previous section, we found the ionospheric/auroral activities at south side of Syowa Station around the onset of the event.…”
Section: Discussionsupporting
confidence: 67%
“…As observed vertical redistribution of existing Na ions is insufficient in serving as a good reservoir for formation of sporadic Na atomic layer [ Kopp , ], horizontal redistribution of ions is proposed by Matuura et al []. This new mechanism seems capable to provide a sufficient reservoir for electrons and metal ions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…If the converged ion layers descend, the lifetime of the sodium ion (within the ion layers) becomes drastically shorter, and the rapid ion neutralization, i.e., neutral sodium atom production, can be induced [ Cox and Plane , ]. More recently, Matuura et al [] suggested a new theory for possible horizontal ion convergence in the field‐aligned current loop system (related with the electric field). The combination of vertical and horizontal convergence would induce faster ion convergence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the wind, the electric field would be another important factor in the polar region, as mentioned above [cf. Kirkwood and von Zahn , ; Cox and Plane , ; Matuura et al , ; Takahashi et al , ]. To clarify these points, we have performed comprehensive observations at Tromsø, Norway (69.6°N, 19.2°E), which includes wind velocity by meteor radar, F region ion velocity, i.e., electric field, by European incoherent scatter (EISCAT) radar, and sodium density profiles at multipositions by multidirectional lidar system.…”
Section: Introductionmentioning
confidence: 99%